The Constructal Law (La Loi Constructale),- Book Review - Reis, A. Heitor (2006)
The new concepts presented in this book, which follows other recent books published by the authors, have already triggered investigations about structure and configuration of flow systems in fields ranging from engineering to economics, and from geophysics to biology and physiology. A growing number of papers reporting advances in these fields based on the Constructal Law have been published in the last years. In the next future we can envisage that new developments will appear because the field of application of the Constructal Law extends flow system to every (living or inanimate).